2018
DOI: 10.1167/iovs.18-23831
|View full text |Cite
|
Sign up to set email alerts
|

SWATH-MS Proteomic Analysis of Oxygen-Induced Retinopathy Reveals Novel Potential Therapeutic Targets

Abstract: The results reveal new potential therapeutic targets to address hypoxia-induced pathological angiogenesis taking place in number of retinal diseases. The extensive proteomic profiling combined with pathway analysis also identifies novel molecular networks that could contribute to the pathogenesis of retinal diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
41
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(44 citation statements)
references
References 71 publications
(101 reference statements)
1
41
1
1
Order By: Relevance
“…Beyond defense against glaucomatous neurodegeneration by β-cystallin(s), their protective role in type 2 epithelial-to-mesenchymal transition of retinal-pigment epithelial cells occurring in dry age-related macular degeneration has been shown recently [60]. However, all crystallins were found to be upregulated in a neonatal mouse model of oxygen-induced retinopathy [61][62][63][64], which indicated a developmental stage-dependent control of their expression. Nevertheless, our data summarized in Figure 3 support the observation about a highly correlated group of α-, β-, and γ-crystallin genes [65].…”
Section: Discussionmentioning
confidence: 99%
“…Beyond defense against glaucomatous neurodegeneration by β-cystallin(s), their protective role in type 2 epithelial-to-mesenchymal transition of retinal-pigment epithelial cells occurring in dry age-related macular degeneration has been shown recently [60]. However, all crystallins were found to be upregulated in a neonatal mouse model of oxygen-induced retinopathy [61][62][63][64], which indicated a developmental stage-dependent control of their expression. Nevertheless, our data summarized in Figure 3 support the observation about a highly correlated group of α-, β-, and γ-crystallin genes [65].…”
Section: Discussionmentioning
confidence: 99%
“…Prior to SWATH analysis method, a relative protein quantification library was built from several data-dependent analysis (DDA) runs with the same LC gradient and instrument settings that were used for SWATH analyses. Before MS runs, samples were subjected to reduction, alkylation, and digestion with calpain protease instead of trypsin as described in detail in Reference [29]. After digestion, peptides were diluted to 14 µl of sample buffer (2% acetonitrile and 0.1% formic acid) and 1 µl of sample was injected to the triple TOF mass spectrometry.…”
Section: Mass Spectrometrymentioning
confidence: 99%
“…We tried to quantify by ELISA some of the growth factors implicated in the blood‐derived stimuli of wound closure, but could not detect them from wound lysates, which is in line with the short half‐life of growth factors in the protease‐rich milieu of the wound . Then, we tried a proteomics‐based approach, but no growth factors were among the detected proteins. This finding is in line with the fact that a 30‐kDa dialysis cut‐off value was used in the processing of tissue samples for proteomics .…”
Section: Discussionmentioning
confidence: 99%
“…Then, we tried a proteomics‐based approach, but no growth factors were among the detected proteins. This finding is in line with the fact that a 30‐kDa dialysis cut‐off value was used in the processing of tissue samples for proteomics . Most recent data have shown that R‐Ras is also crucial for lumenization of new capillaries and microvessels in ischaemic conditions .…”
Section: Discussionmentioning
confidence: 99%